2008
DOI: 10.1007/s12274-008-8038-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nucleases on the cellular internalization of fluorescent labeled DNA-functionalized single-walled carbon nanotubes

Abstract: Nuclease effects on the cell internalization of single-walled carbon nanotubes (SWNTs) functionalized with fluorescent-labeled DNA in serum containing cell growth media were examined. When Cy3-labeled DNAfunctionalized SWNT conjugates (Cy3DNA-SWNTs) were incubated with HeLa cells in a fatal bovine serum (FBS) medium, a high fl uorescence intensity was obtained from the cells, indicative for the high level inclusion of Cy3DNA-SWNTs. However, the fluorescence intensity was remarkably reduced if Cy3DNA-SWNTs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Liu et al showed previously that DNA could be immobilized on pyrene derivatives of functionalized CNTs[ 44 ]. Other than these pyrene derivatives, single stranded DNA can also be used to immobilize CNTs[ 45 ], however DNA can be cleaved by serum, suggesting non-covalent reactions may not be stable in some cases[ 46 ]. For covalent binding, reactive groups are usually formed by various oxidation methods[ 37 , 47 ] which allow for further modifications to enhance polymer[ 38 ], protein[ 48 ] and DNA[ 33 ] attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al showed previously that DNA could be immobilized on pyrene derivatives of functionalized CNTs[ 44 ]. Other than these pyrene derivatives, single stranded DNA can also be used to immobilize CNTs[ 45 ], however DNA can be cleaved by serum, suggesting non-covalent reactions may not be stable in some cases[ 46 ]. For covalent binding, reactive groups are usually formed by various oxidation methods[ 37 , 47 ] which allow for further modifications to enhance polymer[ 38 ], protein[ 48 ] and DNA[ 33 ] attachment.…”
Section: Resultsmentioning
confidence: 99%
“…39 However, there are reports suggesting that noncovalent binding of biological molecules may not remain stable in serum containing situations. 40 Thus, based on our goal to provide cell attachment sites on CNTs, we functionalized CNTs through covalent reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have utilized this pi-pi interaction to noncovalently bind the CNT surface to porphyrin (71) or pyrene (72)(73)(74), which later allowed for further functionalization of proteins on the CNT surface. Other noncovalent bonding included pi-pi stacking between the CNT surface and DNA (75), although there have been concerns regarding the serum stability of DNA-wrapped CNTs owing to potential enzyme activity that may degrade the DNA wrapping (76). Amphiphilic polysaccharides and their derivatives, such as starch (77) and dextran sulfate (78), have also been employed to enfold SWNTs, enhancing their biocompatibility and solubility in biological solutions and mitigating their potential toxicity.…”
Section: Functionalization Of Cnts and Its Hybridsmentioning
confidence: 99%